Changes in JC virus-specific T cell responses during natalizumab treatment and in natalizumab-associated progressive multifocal leukoencephalopathy - Perkins,MR; Ryschkewitsch,C; Liebner,JC; Monaco,MCG; Himelfarb,D; Ireland,S; Roque,A; Edward,HL; Jensen,PN; Remington,G; Abraham,T; Abraham,J; et al. (PLoS Pathogens, 2012)
Progressive multifocal leukoencephalopathy (PML) induced by JC virus (JCV) is a risk for natalizumab-treated multiple sclerosis (MS) patients. Here we characterize the JCV-specific T cell responses in healthy donors and natalizumab-treated MS patients to reveal functional differences that may account for the development of natalizumab-associated PML. CD4 and CD8 T cell responses specific for all JCV proteins were readily identified in MS patients and healthy volunteers. The magnitude and quality of responses to JCV and cytomegalovirus (CMV) did not change from baseline through several months of natalizumab therapy. However, the frequency of T cells producing IL-10 upon mitogenic stimulation transiently increased after the first dose. In addition, MS patients with natalizumab-associated PML were distinguished from all other subjects in that they either had no detectable JCV-specific T cell response or had JCV-specific CD4 T cell responses uniquely dominated by IL-10 production. Additionally, IL-10 levels were higher in the CSF of individuals with recently diagnosed PML. Thus, natalizumab-treated MS patients with PML have absent or aberrant JCV-specific T cell responses compared with non-PML patients, and changes in T cell-mediated control of JCV replication may be a risk factor for developing PML. Our data suggest further approaches to improved monitoring, treatment and prevention of PML in natalizumab-treated patients.